2020
DOI: 10.1007/s00330-020-07289-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance T2 mapping and feature tracking in athlete’s heart and HCM

Abstract: Objectives Distinguishing hypertrophic cardiomyopathy (HCM) from left ventricular hypertrophy (LVH) due to systematic training (athlete’s heart, AH) from morphologic assessment remains challenging. The purpose of this study was to examine the role of T2 mapping and deformation imaging obtained by cardiovascular magnetic resonance (CMR) to discriminate AH from HCM with (HOCM) or without outflow tract obstruction (HNCM). Methods Thirty-three patients with HOCM, 9 with HNCM, 13 strength-trained athletes as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…T2 mapping, however, demonstrates myocardial or interstitial water content with variations in signal intensity being useful in differentiating between different cardiac diseases [ 44 ]. In HCM, higher T2 values are reported, with the differences being accounted for on a structural level, which are purported to reflect myocyte degeneration, disarray, and replacement fibrosis [ 45 ]. In addition, it frequently corresponds with LGE, which may explain the process of initial dysfunction in HCM and the subsequent progression to fibrosis [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…T2 mapping, however, demonstrates myocardial or interstitial water content with variations in signal intensity being useful in differentiating between different cardiac diseases [ 44 ]. In HCM, higher T2 values are reported, with the differences being accounted for on a structural level, which are purported to reflect myocyte degeneration, disarray, and replacement fibrosis [ 45 ]. In addition, it frequently corresponds with LGE, which may explain the process of initial dysfunction in HCM and the subsequent progression to fibrosis [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…T1/T2 mapping is a method of quantifying tissue properties while FT is used to quantify LV regional function, and both have different purposes. Accordingly, some studies have reported that T1/T2 mapping and FT are complementary and that their combined use leads to improved lesion detection 30,31 . We also plan to combine these 2 methods in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…LA conduit function was already impaired at early stages, therefore, representing the most sensitive LA strain parameter for early detection of fibrosis in HCM patients [72]. As another approach underlining benefits of CMR technique for diagnostic purposes, a multiparametric approach combining various CMR-FT and structural analyses provided important information for discrimination between HCM and athlete's cardiomyopathy [73]. Interestingly, in exercise-induced hypertrophied athlete's hearts, both LV and RV strain assessments even revealed differences between athletes of different sport disciplines [74], underlining the importance of comprehensive deformation analyses to capture and classify different exercise-induced myocardial adaptions of all cardiac chambers and to enable a distinction from hypertrophy of life-threatening cardiomyopathies [75].…”
Section: Cmr-ft In Non-ischemic Cardiomyopathiesmentioning
confidence: 99%